2020
DOI: 10.3389/fnagi.2020.00170
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Bone Marrow Mononuclear Cells Transplantation in Aged Mice Increases Transcription of Glucose Transporter 1 and Na+/K+-ATPase at Hippocampus Followed by Restored Neurological Functions

Abstract: We recently reported that intravenous bone marrow mononuclear cell (BM-MNC) transplantation in stroke improves neurological function through improvement of cerebral metabolism. Cerebral metabolism is known to diminish with aging, and the reduction of metabolism is one of the presumed causes of neurological decline in the elderly. We report herein that transcription of glucose transporters, monocarboxylate transporters, and Na + /K +-ATPase is downregulated in the hippocampus of aged mice with impaired neurolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 25 publications
(35 reference statements)
2
21
0
Order By: Relevance
“…BM-MNC transplantation promotes angiogenesis/neovascularization in the several ischemic diseases, such as limb ischemia and myocardial infarction, even if they are not in the acute phase (19,20). In addition, we demonstrated that the therapeutic mechanisms of BM-MNC include energy source to injured cells and angiogenesis activation in damaged endothelial cells (6). Therefore, we hypothesized that the therapeutic effect associated with angiogenesis may occur in chronic stroke.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…BM-MNC transplantation promotes angiogenesis/neovascularization in the several ischemic diseases, such as limb ischemia and myocardial infarction, even if they are not in the acute phase (19,20). In addition, we demonstrated that the therapeutic mechanisms of BM-MNC include energy source to injured cells and angiogenesis activation in damaged endothelial cells (6). Therefore, we hypothesized that the therapeutic effect associated with angiogenesis may occur in chronic stroke.…”
Section: Discussionmentioning
confidence: 94%
“…In our previous study, we showed that the transfer of low molecular weight substances, including glucose, from transplanted BM-MNC to cerebral endothelial cells is the prominent pathway in the activation of endothelial cells by BM-MNC transplantation after cerebral ischemia (5). In addition, the transplant of BM-MNC restored the neurological function by activating transcription of major energy supply and consumption-related genes in the brain (6). Therefore, we hypothesized that BM-MNC might have a therapeutic effect in the case of the chronic phase of stroke.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, we showed that intravenously injected BM-MNC supplies an energy source, such as glucose, to endothelial cells via gap junction and activates injured endothelial cells by induction of hypoxia inducible factor 1-α (Hif1-α), which is one of the major activators of metabolism related genes (Kim et al, 2006), in a cerebral ischemia model (Kikuchi-Taura et al, 2020). Intravenous BM-MNC transplantation in aged mice was shown to increase transcription of glucose transporter 1 (Glut1) at hippocampus followed by improved memory functions through gap junction mediated cell-cell interaction between transplanted BM-MNC and endothelial cells (Takeuchi et al, 2020). Furthermore, we have shown that intravenously transplanted mesenchymal stem cells remove the energy source from endothelial cells via gap junction, and suppress their excessive activation in a cerebral ischemia model (Kikuchi-Taura et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative PCR (qPCR) Analysis of Circulating White Blood Cells, Hippocampus, and Human Umbilical Vein Endothelial Cells Male CB-17 mice (C.B-17/Icr-+ / + Jcl, Oriental Yeast, Tokyo, Japan) aged 5, 10, 52, and 104 weeks were used for this study (N = 5, each). Minimal variation of cerebrovascular structure is known in CB-17 mice (Taguchi et al, 2010) and CB-17 mice were used for the experiment of cerebrovascular disorders (Kasahara et al, 2013;Takeuchi et al, 2020). After deep anesthesia by pentobarbital, a blood sample was obtained by the puncture to left ventricle of heart.…”
Section: Introductionmentioning
confidence: 99%
“…With the resurgence of phenotypic assays in drug discovery, the observations in these systems are often complex as recently shown by cell-cell interactions in stroke models ( Kikuchi-Taura et al, 2020 ; Takeuchi et al, 2020 ; Kikuchi-Taura et al, 2021 ) and understanding the nature of the PPIs using novel technologies will allow the scientific community to better understand and unveil therapeutically relevant aspects of such PPIs to treat a variety of human diseases.…”
mentioning
confidence: 99%